Fibonacci lengths of all finite p-groups of exponent p^2 - Ahmadi, B.; Doostie, H. (Ukrains’kyi Matematychnyi Zhurnal, 2013)
The Fibonacci lengths of finite p-groups were studied by Dikici and coauthors since 1992. All considered groups are of exponent p and the lengths depend on the Wall number k(p). The p-groups of nilpotency class 3 and exponent p were studied in 2004 also by Dikici. In the paper, we study all p-groups of nilpotency class 3 and exponent p^2. Thus, we complete the study of Fibonacci lengths of all p-groups of order p^4 by proving that the Fibonacci length is k(p^2).